The differentiation between freshwater and marine fish trypanosomes by lectin agglutinability - Zajícek, P; Lukes, J (Folia parasitologica, 1992)
The agglutinability of three fish trypanosomes, Trypanosoma boissoni and T. triglae senegalensis from marine fish, and T. carassii from freshwater fish was compared. The tests were performed with trypomastigotes and epimastigotes in the exponential and stationary growth phases. The simple agglutination test, performed in microwell plates, used ten purified lectins, and revealed a clear difference between marine and freshwater strains when compared for their agglutinability with the HPA lectin. Whereas the cells of T. boissoni and T. triglae senegalensis became strongly agglutinated by this lectin, those of T. carassii remained unagglutinated in the same conditions. However, the cells of T. triglae senegalensis reacted positively with ConA lectin in the stationary phase only. The differences in structure and composition of surface polysaccharides stable after prolonged cultivation in vitro are inferred on the basis of the results obtained.
Keywords: Agglutination Tests; Fishes; Animals; Lectins; lektiny; zvířata; aglutinační testy; ryby; Trypanosoma